SCIENCE AND TECHNOLOGY IN AFRICA FOR THE TWENTY FIRST CENTURY: PERSPECTIVES FOR CHANGE - Ogunseemi, Olatunbosun Emmanuel (European Scientific Journal, ESJ, 2015)
There is no doubting that the role of science and technology in modern society is changing. More importantly, all the challenges facing the world and communities in Africa particularly today depends solely on science and technology education to find appropriate solution. It is noteworthy in this century that nations will wholly dependent on others as ‘experts’ without science and technological knowledge. But with it, they will be empowered to become participants rather than merely observers. Science and technology in this sense is more than a means for getting ahead in the world of work. It is a resource for becoming a critical and engaged citizen in a democracy. However to realize this, the teaching of science and technology in schools should help in development of science and technology literacy. Also in the formation of scientific and technological attitude, this is essential to dispel social evils as well as in the development of open mindedness and decision taking ability. Therefore, this study suggests the teaching and learning of science and technology in schools with the looking glass of 21st century skills for efficient pedagogical format and content responsibility by the teachers and the society. This perspective involves the position of government as policy formulators, the teachers as policy implementers and disseminators as well as the society as policy facilitators.